Skripsi hubungan antara spiritualitas dengan tingkat stres pada mahasiswa keperawatan dan kebidanan yang mengerjakan tugas akhir di politeknik kesehatan banten: hubungan antara spiritualitas dengan tingkat stres pada mahasiswa keperawatan dan kebidanan yang mengerjakan tugas akhir di politeknik kesehatan banten (Midwinerslion : Jurnal Kesehatan STIKes Buleleng, 2021)
ABSTRACT Background: In Indonesia who experienced depression or stress disorder in 2013 for those aged more than 15 years reached 14 million people or the equivalent of 6% of the population in Indonesia. At the Faculty of Health Sciences, Muhammadiyah University of Tangerang, there are 60% students who experience moderate stress category and 40% students who experience mild stress category. Research Objectives: To determine the relationship between spirituality and stress levels in students who do final projects at Banten Health Polytechnic. Methods: The sampling technique used in this study was incidental sampling with a total of 140 respondents. Results: The results of this study showed that 30 respondents (49.2%) had low spirituality with low stress levels, while respondents who had low spirituality with high stress levels 31 respondents (50.8%). Respondents who have high spirituality with low stress levels are 52 respondents (65.8%) while respondents who have high spirituality with high stress levels are 27 respondents (34.2%). The results of the chi-square test showed a relationship between spirituality and stress levels in students who did their final project (p-value = 0.044 <0.05). Conclusions and suggestions: Most respondents have characteristics of high spirituality with low stress levels. Students or female students are expected to always strengthen their spirituality well, considering that students or female students are prone to stress due to their final assignments. So, by strengthening spirituality properly can prevent stress. Keywords: Spirituality, Stress Level